2016
DOI: 10.3174/ajnr.a4840
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Aspiration, First Pass Technique (ADAPT) versus Stent Retrievers for Acute Stroke Therapy: An Observational Comparative Study

Abstract: BACKGROUND AND PURPOSE:Mechanical thrombectomy with stent retrievers is now the standard therapy for selected patients with ischemic stroke. The technique of A Direct Aspiration, First Pass Technique for the Endovascular Treatment of Stroke (ADAPT) appears promising with a high rate of recanalization. We compared ADAPT versus stent retrievers (the Solitaire device) for efficacy and safety as a front-line endovascular procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
87
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 26 publications
10
87
3
3
Order By: Relevance
“…26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] We aimed to identify patients in whom the aspiration component of ADAPT is most likely to be successful.…”
mentioning
confidence: 99%
“…1) Additionally, high recanalization rates have been reported by the a direct aspiration first pass technique (ADAPT), 7,8) which is a modification of the conventional procedure using the Penumbra system. However, acute occlusion of major intracranial arteries may be caused by embolic lesions that cannot be recanalized by the above devices as well as atherosclerotic lesions and arterial dissection.…”
Section: Discussionmentioning
confidence: 99%
“…It may be concerned that the deflection of used device influenced safety because a retrospective study reported a lower rate of symptomatic hemorrhage for contact aspiration compared with stent retrievers. 13) A stent retriever is a device which must be placed within a microcatheter across the occluded segment once before expanded. Furthermore, vessels are stretched to some degree while withdrawing the device.…”
Section: Discussionmentioning
confidence: 99%